The role of German idealism in Žižek's transcendental materialism - Carew, Joseph, 1986- (2010)
Thesis (M.A.)--Memorial University of Newfoundland, 2010. -- Philosophy "February 2010." -- Typescript. -- Includes bibliographical references (leaves 92-93).